2017
DOI: 10.1063/1.4989627
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evaporation-driven chemical pre-concentration and separation on paper

Abstract: Airflow-enhanced evaporation is investigated as a method for rapid chemical pre-concentration on a thin porous substrate. The mechanism is described by combining 1D models of capillary rise, chromatography and pervaporation concentration. It is shown that the effective length of the column can be shorter than its actual length, allowing concentrate to be held at a stagnation point and then released for separation, and that the Péclet number, which determines concentration performance, is determined only by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 61 publications
(64 reference statements)
1
17
0
Order By: Relevance
“…Various strategies were developed over the past 20 years to design and integrate such evaporation surfaces in order to enhance the efficiency of evaporation-based microfluidic pumps. One can cite, for instance, microporous hydrophilic membranes, filter papers, hydrophilic porous materials as shown in Figure , microfabricated arrays of micropores, , or even simply splitting the main channel into an array of open channels with small transverse dimensions, , as illustrated in Figure .…”
Section: Microfluidic Passive Pumpingmentioning
confidence: 99%
See 2 more Smart Citations
“…Various strategies were developed over the past 20 years to design and integrate such evaporation surfaces in order to enhance the efficiency of evaporation-based microfluidic pumps. One can cite, for instance, microporous hydrophilic membranes, filter papers, hydrophilic porous materials as shown in Figure , microfabricated arrays of micropores, , or even simply splitting the main channel into an array of open channels with small transverse dimensions, , as illustrated in Figure .…”
Section: Microfluidic Passive Pumpingmentioning
confidence: 99%
“…This flow in turn increases the pressure drop associated with viscous forces and can modify the imbibition dynamics. In the case of a simple strip of paper partially immersed in a water tank, for example, evaporation can stop the dynamics of liquid imbibition at a given position, ,,, as detailed in section .…”
Section: Microfluidic Passive Pumpingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be shown that diffusion phenomena in homogeneous materials obey a parity symmetry, which means that diffusion, in homogeneous media, occurs identically along the positive and negative directions of a given axis 2 . One way to break such a symmetry has been shown to be the use of a moving medium; for instance, showing an asymmetric diffusion of chemical solutions within airflow 3 . Therefore, let us pose the following question: can we design an effectively homogenized material in which diffusion would have a spatially directional preference?…”
Section: Introductionmentioning
confidence: 99%
“…Multiple-step competitive ELISA for Imidacloprid detection is successfully conducted with a similar sensitivity to the ELISA procedures done in plates. The device can be further improved and extended its capability of performing detection for clinical or environmental analytes [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%